Gonadal hormones may predict structural bone fragility in elite female soccer player - Lanhers, C.; Courteix, D.; Valente-dos-Santos, J.; Ferry, B.; Gracia-Marco, L.; Pereira, B.; Borda, I. M.; Lespessailles, E.; Duclos, M. (Journal of Sports Sciences, 2020)
Purpose: This study determined the impact of menstrual status on bone tissue in elite post-pubertal female soccer players over an entire season.